Lifetime serum concentration of 25-hydroxyvitamin D 25(OH) is associated with hand grip strengths: insight from a Mendelian randomisation. (9th April 2022) - Mazidi, Mohsen; Davies, Ian G; Penson, Peter; Rikkonen, Toni; Isanejad, Masoud
Abstract: Clinical trials have suggested that increased 25-hydroxyvitamin D (25(OH)D) has positive effect on hand grip strength. This Mendelian randomisation (MR) was implemented using summary-level data from the largest genome-wide association studies on vitamin D ( n  = 73, 699) and hand grip strength. Inverse variance weighted method (IVW) was used to estimate the causal estimates. Weighted median (WM)-based method, MR-Egger and leave-one-out were applied as sensitivity analysis. Results showed that genetically higher-serum 25(OH)D levels had a positive effect on both right hand grip (IVW = Beta: 0.038, P  = 0.030) and left hand grip (IVW = Beta: 0.034, P  = 0.036). There was a low likelihood (statistically insignificant) of heterogeneity and pleiotropy, and the observed associations were not driven by single single-nucleotide polymorphisms. Furthermore, MR pleiotropy residual sum and outlier did not highlight any outliers. In conclusion, our results highlighted the causal and beneficial effect of serum 25(OH) D on right- and left-hand grip strengths.